Peran Tes Bakat dalam Pengembangan Diri dan Pendidikan - Jenisa Dwi Ameilia Viga; Yeshaya Sahda Eka Agatha; Suhailah Ainur Rohmah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Talent is a fundamental ability that exists within an individual from the beginning, but it still needs to be developed through practice and learning. Talent is special because not everyone possesses it in the same form, and each individual has a unique talent. Since talent significantly influences learning success, it is important for educators, especially guidance counselors, to understand and assist students in recognizing and developing their inherent talents. This way, the learning process can become more effective and aligned with each student's potential. The objective of this study is to obtain a descriptive result of the role of aptitude tests in personal development and education. The method used is a qualitative approach with a literature study type. This literature review examines journals, books, and other documents that provide a comprehensive overview of theories and current information on a topic, encompassing perspectives from both the past and present. The research findings include: (1) definitions of aptitude tests, (2) types of aptitude tests, (3) challenges and limitations of aptitude tests, (4) factors influencing talent, (5) benefits of aptitude tests, (6) the role of aptitude tests in personal development, and (7) the role of aptitude tests in education.